Statistical Evaluation of the Equivalence Scale Based on Joint Accommodation for Households of the Russian Federation - Beglova, Elena Irekovna; Sadyrtdinov, Ruslan Raisovich; Guseva, Lubov Akimovna (International Journal of Economics and Financial Issues, 2015)
In this article an evaluation of equivalence scales for households of the Russian Federation is made using the data from “Russian monitoring of the economic situation and public health HSE (RLMS-HSE)” for the year 2013. Calculation of equivalence scales is done through a regression estimate of the Engel curve. Identified on the basis of the value of the resulting regression model scale are significantly different from the official scale of the Federal State Statistics Service of the Russian Federation. The authors have shown that it has significant implications for the evaluation of the relative poverty of certain vulnerable groups, in turn, has great significance for the implementation of targeted social policies. Keywords: equivalence scale, poverty, household, economies of scale, inequality, the Russian Federation JEL Classifications: C83; C35; D63; D14; H31